Health Signage, Linguistic Exclusion, and the Politics of Biomedical Access in Multilingual Southern Taraba, Nigeria: A Linguistic Landscape Analysis - Judith Adaku Mgbemena; Azetu Azashi Agyo; Vika Tensaba Akafa (CV. Rustam, 2026)
Health-facility signage in multilingual postcolonial societies does more than instruct patients: it allocates communicative authority, marks the languages of biomedical legitimacy, and determines whose linguistic repertoire counts as adequate for independent engagement with the written health-care environment. This study examines how language choice in health signage constructs a stratified semiotic order in Southern Taraba State, Nigeria, drawing on a photographic corpus of one hundred and ten items documented across primary health-care centres, referral hospitals, a federal teaching hospital, private medical facilities, and NGO premises spanning Ibi, Wukari, Takum, Donga, and Ussa Local Government Areas. Using a qualitative multi-site linguistic landscape design, the study analyses signage across five dimensions: producer category, language choice, communicative register, spatial emplacement, and health literacy implications. The analysis is theorised through linguistic landscape theory (Landry & Bourhis, 1997; Ben-Rafael et al., 2006), geosemiotics (Scollon & Scollon, 2003), orders of indexicality (Blommaert, 2010), postcolonial critiques of development discourse (Escobar, 1995; Mignolo, 2000), and health literacy theory (Nutbeam, 2000). The findings demonstrate that English dominates health signage across all producer categories such as governmental, international-donor, NGO, pharmaceutical, and private, while the indigenous community languages of Southern Taraba (Jukun, Kuteb, Tiv, Chamba) are entirely absent from all documented signage. Two items introduce Hausa, a regional lingua franca, as a partial secondary code, revealing a graduated linguistic hierarchy. The article introduces graduated structural exclusion — the condition in which selective lingua franca accommodation performs multilingual outreach while leaving indigenous language marginalisation intact — as a contribution to linguistic landscape studies, postcolonial health communication scholarship, and language planning policy.